WEBGIS OF MAPPING PASURUAN CITY FURNITURE INDUSTRY USING LEAFLET AND OPENSTREETMAP - Junikhah, Allin; Hayati Holle, Khadijah Fahmi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Pasuruan is a well-known area for producing furniture products in East Java. The furniture commodity industry is widely spread in this city. This industry is also one of the top products. To boost market interest in the furniture industry in Pasuruan City, which has been affected by the COVID-19 pandemic, and a geographic information system has not yet been developed in an effort to develop the furniture industry, research has been carried out on a web-based geographic information system (WebGIS) mapping the furniture industry in Pasuruan City using Leaflets and OpenStreetMap. The developed furniture industry WebGIS application takes advantage of the open source and dynamic advantages of Leflet and OpenStreetMap technologies which have provided very decent results on several GIS web-based application systems. In the testing phase with the Blackbox method, the WebGIS application for the furniture industry in Pasuruan City functionally has run well on desktop devices and also run well on simulated mobile devices. Testing was carried out on several types of browsers like Google Chrome and Microsoft Edge. This WebGIS application has been able to map the furniture industry in Pasuruan City so that the distribution of economic activity actors, especially the furniture industry, can be seen throughout the city and each sub-district. It can provide detailed information on furniture industry players in Pasuruan.            Keywords: framework; leaflet; mapping; openstreetmap; webgis  Abstrak: Pasuruan merupakan salah satu daerah yang terkenal sebagai penghasil produk mebel di Jawa Timur. Industri komoditas mebel tersebar cukup banyak di kota ini. Industri ini juga merupakan salah satu produk unggulan. Guna mendongkrak minat pasar akan industri mebel kota Pasuruan yang terimbas pandemi COVID-19, dan belum dikembangkannya suatu sistem informasi geografis sebagai upaya pengembangan industri mebel maka dilaksanakan penelitian tentang sistem informasi geografis berbasis web (WebGIS) pemetaan industri mebel kota Pasuruan menggunakan Leaflet dan OpenStreetMap. Aplikasi WebGIS industri mebel yang dikembangkan memanfaatkan kelebihan teknologi Leflet dan OpenStreetMap yang bersifat open source dan dinamis yang telah memberikan hasil yang sangat layak pada beberapa sistem aplikasi berbasis WebGIS. Pada tahap pengujian dengan metode Blackbox, aplikasi WebGIS industri mebel kota Pasuruan secara fungsional telah dapat berjalan dengan baik pada perangkat dekstop dan juga berhasil berjalan dengan baik pada simulated mobile device. Pengujian dilakukan pada beberapa macam browser seperti Google Chrome dan Microsoft Edge. Aplikasi WebGIS ini telah dapat memetakan industri mebel kota Pasuruan, sehingga dapat diketahui sebaran pelaku kegiatan ekonomi khususnya industri mebel, baik seluruh kota maupun tiap-tiap kecamatan, serta dapat memberikan detail informasi pelaku industri mebel di kota Pasuruan. Kata kunci: framework; leaflet; openstreetmap; pemetaan; webgis